A potential urinary biomarker to determine frailty status among older adults. (May 2020) - Jiang, Shan; Kang, Lin; Zhu, Minglei; Zhang, Xu; Wang, Chenchen; Cai, Jianping; Liu, Xiaohong
Highlights: 8-oxo-7, 8-dihydroguanosine (8-oxo-Gsn), the oxidative adduct derived from RNA, is a biomarker of RNA oxidative damage. 8-oxo-Gsn can be tested in urine and the test is non-invasive. Urinary 8-oxo-Gsn level was independently associated with frailty among older adults. This urinary biomarker is a good indicator of frailty status, especially combining a simple question evaluating exhaustion, which can provide the optimal predictive value for frailty. Abstract: Background: Association of oxidative stress biomarkers with aging and several age-related diseases is well documented. However, the possible role of these factors on frailty status in older adults has not been extensively studied. Objective: To evaluate whether urinary 8-oxo-7, 8-dihydroguanosine (8-oxo-Gsn), a biomarker of RNA oxidative damage, was independently associated with frailty. Methods: In this cross-sectional analysis, frailty phenotype was assessed among 230 participants living in a senior community. Participants received a comprehensive geriatric assessment. Serum high-sensitivity C-reactive protein (hsCRP), white blood cell count (WBC), urinary 8-oxo-7, 8-dihydro-2′-deoxyguanosine, and 8-oxo-Gsn were measured. Results: Participants' mean age was 83.9 ± 4.4 years. In total, 33 % were frail, 45 % were pre-frail, and 22 % were non-frail. Urinary 8-oxo-Gsn, serum hsCRP, and WBC were significantly higher in the frail group than in the non-frail and pre-frail groups (p-values < 0.05). Adjusting for age, sex, and Charlson comorbidity index, statistically significant positive associations with frailty were observed for urinary 8-oxo-Gsn (odds ratio [OR]: 1.70, 95 % confidence interval [CI]: 0.264–0.732) and hsCRP (OR: 1.337, 95 % CI: 0.089–0.412). Urinary 8-oxo-Gsn of 3.175 μmol/mol had the optimal predictive value for frailty, with an area under the receiver operating characteristic curve (AUC) of 0.72 (95 % CI: 0.649–0.788). The prediction probability combining urinary 8-oxo-Gsn and a simple question evaluating exhaustion had the optimal predictive value for frailty, with an AUC of 0.90 (p < 0.001, 95 % CI: 0.85–0.95). Conclusion: Urinary 8-oxo-Gsn level was independently associated with frailty. This urinary biomarker may be a promising indicator of frailty.